Microplastics in Kenya's marine nearshore surface waters: Current status. (June 2022) - Kosore, Charles Mitto; Ojwang, Loice; Maghanga, Justin; Kamau, Joseph; Shilla, Daniel; Everaert, Gert; Khan, Farhan R.; Shashoua, Yvonne
Abstract: Microplastics (MPs) were collected at six locations along Kenya's marine nearshore surface waters using a 300 μm mesh-size manta net. The samples were washed over a 125-μm mesh size sieve No.120 into a glass jar and preserved in 70% ethanol. MPs were sorted, counted visually under a dissecting microscope then identified using attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy. A total of 1473 particles with an overall mean concentration of 0.58 ± 1.29 MPs m −3, were collected. Fragments were the most common types representing 55% of the total MPs, followed by films (40%) and fibers (2%). Polypropylene (PP) was dominant (52%), high-density polyethylene (HDPE) comprised 38% and low density polyethylene (LDPE) 10% of the total MPs. This study provided baseline information, in which Malindi was identified as a hot spot for MPs pollution. Furthermore, the outcomes will assist policy formulations and management strategies aimed at controlling marine plastics. Highlights: One of the first baseline quantifications of MPs in Kenya's nearshore waters The abundance of MPs at Malindi identified it as a hotspot. Fragments and films dominate the types of MPs. River inputs influence distribution of MPs.